2013
DOI: 10.1002/aoc.2968
|View full text |Cite
|
Sign up to set email alerts
|

Titanium–salan‐catalyzed asymmetric sulfoxidations with H2O2: design of more versatile catalysts

Abstract: Titanium–salan complexes with 3,3’‐diphenyl substituents in the salicylidene rings of the salan ligand are efficient sulfoxidation catalysts, capable of catalyzing the asymmetric oxidation of bulky aryl benzyl sulfides with H2O2 with good to high enantioselectivities. In this paper, substituent effects on titanium‐salan‐catalyzed enantioselective oxidation of sulfides to sulfoxides have been systematically investigated. Titanium–salan catalysts with halogen substituents at the 5,5’‐positions (3,3’‐H2dihydrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…For instance, a peroxotitanium(IV) reactive intermediate was predicted by DFT calculations in a titanium–salan based catalyst system for (nonstereoselective) sulfoxidation, and its formation was corroborated by atmospheric‐pressure chemical ionization mass spectrometry studies 31. Talsi and Bryliakov studied the kinetics of parallel oxidation of various sulfides on titanium–salan catalysts and concluded that, under those reaction conditions (−10 °C, C Ti =10 −4 M ), the reaction is rate‐limited by the reaction of H 2 O 2 with the chiral Ti complex to form the active oxidant 21. The latter rapidly reacts further with the sulfide.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…For instance, a peroxotitanium(IV) reactive intermediate was predicted by DFT calculations in a titanium–salan based catalyst system for (nonstereoselective) sulfoxidation, and its formation was corroborated by atmospheric‐pressure chemical ionization mass spectrometry studies 31. Talsi and Bryliakov studied the kinetics of parallel oxidation of various sulfides on titanium–salan catalysts and concluded that, under those reaction conditions (−10 °C, C Ti =10 −4 M ), the reaction is rate‐limited by the reaction of H 2 O 2 with the chiral Ti complex to form the active oxidant 21. The latter rapidly reacts further with the sulfide.…”
Section: Resultsmentioning
confidence: 86%
“…The latter rapidly reacts further with the sulfide. The oxidation of sulfide by the electrophilic active species (with Hammett ρ values of −1.35 to −1.40) was concluded to proceed through an oxygen‐transfer mechanism 21…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bryliakov and Talsi reported a simple and efficient catalytic procedure for the oxidation of bulky thioethers with hydrogen peroxide2 [99,100]. This has been achieved by reducing the steric bulk of the salicylidene rings [100].…”
Section: Titanium Catalystsmentioning
confidence: 99%
“…On the other hand, various oxidants such as selenium oxide (SeO 2 ), nitric acid, permanganates, hydrogen peroxide, and oxygen are used for the oxidation of sulfides . Among them, aqueous hydrogen peroxide (H 2 O 2 ) is the most attractive because of safety with the low expense, the high content of effective oxygen, being environment‐friendly, easily available reagent, and also it generates water as the only by‐product . We have also examined the close intermolecular contacts between the molecules in the crystal packing of 1 using Hirshfeld surface analysis.…”
Section: Introductionmentioning
confidence: 99%